Unraveling the role of cAMP signaling in Giardia: insights into PKA-mediated regulation of encystation and subcellular interactions - Han-Wei Shih; Germain C. M. Alas; Alexander R. Paredez (mSphere)
ABSTRACT cAMP plays an important role as a second messenger in the stage transition of various protozoan parasites. This signaling pathway relies on multiple effectors, such as protein kinase A (PKA), exchange protein activated by cAMP, and cAMP-response element binding protein transcription factors, to initiate signal transduction in humans. The Giardia genome only contains two adenylate cyclases (ACs), a single phosphodiesterase (PDE) and a single known PKA effector, and the specific functions of these components are not fully understood. In our previous research, we demonstrated the important role of AC2-dependent cAMP signaling in promoting the encystation program. Using the NanoBit technology, we emphasized the significance of AC2-dependent cAMP biosynthesis in regulating the dissociation of the PKA regulatory domain (PKAr) and PKA catalytic domain (PKAc). In this study, our objectives are twofold: first, we used the newly developed Split-Halo to examine subcellular interactions of GlPKAr and GlPKAc in Giardia; and second, we investigated whether PKAc regulates encystation-specific proteins. Our findings revealed distinct subcellular locations where GlPKAr and GlPKAc interacted during the trophozoite stage, including the flagella, basal bodies, and cytoplasm. Upon exposure to encystation stimuli, the interaction shifted from the flagella to the cytosol. Knockdown of GlPKAc resulted in the downregulation of encystation-specific genes, leading to the production of fewer viable and water-resistant cysts indicating a role for PKA in the transcriptional regulation of encystation. These discoveries contribute to a deeper understanding of the cAMP signaling pathway and its important role in governing Giardia’s encystation process.IMPORTANCEThe precise timing of interactions and subcellular compartmentation play crucial roles in signal transduction. The co-immunoprecipitation assay (CO-IP) has long been utilized to validate protein–protein interactions; however, CO-IPs lack spatial and temporal resolutions. Our recent study used the NanoBit assay, which showcased the reversible protein–protein interaction between PKAr and PKAc in response to cAMP analogs and encystation stimuli. Expanding on this groundwork, this study employs the Split-Halo assay to uncover the subcellular compartments where the PKAr and PKAc protein–protein interactions take place and respond to encystation stimuli. Taken together, these molecular tools provide spatiotemporal information on the protein–protein interaction, which will be useful in the field.